The influence of observers’ sex on attention-demanding performance depends on performers’ sex - Wang, Lijun; Tan, Jinfeng; Chen, Jiangtao; Chen, Antao (Frontiers in Psychology, 2015)
Post-error slowing (PES) indicates the slower responses after errors than after correct responses. Prior studies mainly focus on how the observation errors influence one own’s performance, there is no study investigating how other’s monitoring influence one own’s performance. Additionally, the issue that whether social context influences the PES effect differently for females and males is still unclear. To address aforementioned issues, we required the participants to interact with a same-sex or opposite-sex partner to complete a color flanker task together (they sat next to each other, Experiment 1). One was the performer (perform the flanker task), and the other was the observer (monitor the error responses of performer). They alternated their roles in two successive blocks. To further verify the role of the interaction context, a control experiment was conducted in the individual context (Experiment 2). The results revealed that (1) larger PES effect was observed in females than in males in the interaction context; (2) the sex difference of PES effect mainly benefited from the opposite-sex interaction; (3) larger PES effect was observed in the interaction context than in the individual context; (4) females’ performances were influenced after an interaction with a same-sex or opposite-sex partner, whereas males’ performances were merely influenced after an interaction with an opposite-sex partner. Taken together, these findings may suggest that (1) interaction context modulates the PES effect differently for females and males; (2) females are more susceptible to social information and hence more effective to adjust the post-error behaviors.